Variación temporal de la condición trófica del lago del Parque Norte, Medellín (Antioquia), Colombia (2010)
ABSTRACT: With the goal of evaluating the change of trophic status and humic condition of the lake in Parque Norte (LPN), Medellín (Antioquia, Colombia), samples from one sampling station situated in the mid-point of the lake were obtained. Samples were collected fortnightly from March to August 2004. Trophic status was evaluated using the indexes of Carlson (TSIC), TSI Modi ed by Toledo et al. (TSIM), the Trophic State Index based on chlorophyll a active (TSI Chl. a), and the attenuation coef cient (K) proposed by Poole and Atkins. The results showed that TSIM better described the trophic status of the lake. The low values of the coef cients of variation of this index [TSIM(DS), CV = 5.9%; TSIM(PT), CV = 19.5%; TSIM(Cl a), CV = 13.5%; TSIM(average), CV = 8.2%] indicated that the LPN did not present a signi cant temporal variation in trophic status during the sampling time and tended to remain in a condition of eutrophication. The attenuation coef cient (K = 2.1 m-1; CV = 21.7%) con rmed this. On the other hand, the TSI (Chl. a) classi ed the lake in a category that oscillated from b mesotrophic to a eutrophic, being again veri ed that a strong tendency existed towards eutrophication. While from the physical and chemical point of view the body of water was not very variable, total phosphorus (TP), total nitrogen (TN) and active chlorophyll a (Chl. a) varied temporarily in a signi cant way (TP, CV = 53%, TN, CV = 85% Chl. a, CV = 63%), that makes them good references for carrying out an approximate description of the dynamics of the biological assemblages in this body of water. Finally, a high variation in the content of humic acids was documented (CV = 63%), and its average value (20.4 g l-1) allowed locating the LPN in the mesohumic category.